FLIPPED CLASSROOM : PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN MOTIVASI BELAJAR PESERTA DIDIK MADRASAH TSANAWIYAH - Shafira Fiscarina Widyasari; Rubhan Masykur; Iip Sugiharta (Journal of Mathematics Education and Science, 2021)
This study aims to improve students' mathematical critical thinking skills and learning motivation through the Flipped Classroom learning model. This research is a kind of Quasi-Experimental Design research. The population in this study were students of class VIII MTs Al Khairiyah Agom, sampling using the Cluster Random Sampling technique obtained two classes from several VIII classes at MTs Al-Khairiyah Agom. As a sample, the experimental class uses flipped classroom, while the control class is learning using the expository learning model. Analysis of the data used in this study used the MANOVA test with the R program. Based on the research analysis results, there was an effect of flipped classroom learning on improving mathematical critical thinking skills and learning motivation of students. The essential mathematical skills of thinking and learning motivation of students who use flipped classroom learning are better than the mathematical critical thinking skills of students who use expository knowledge. Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan berfikir kritis matematis dan motivasi belajar peserta didik melalui model pembelajaran Flipped Classroom. Penelitian ini merupakan penelitian jenis Quisi Experimental Design. Populasi pada penelitian ini yaitu peserta didik kelas VIII MTs Al Khairiyah Agom, pengambilan sampel menggunakan  teknik Cluster Random Sampling didapat dua kelas dari beberapa kelas VIII di MTs Al-Khairiyah Agom. Sebagai sampel kelas eksperimen yaitu pembelajaran menggunakan flipped classroom, sedangkan kelas kontrol yaitu pembelajaran menggunakan model pembelajaran ekspositori. Analisis data yang digunakan dalam penelitian ini menggunakan uji MANOVA dengan program R. Berdasarkan hasil analisis penelitian terdapat pengaruh pembelajaran flipped classroom terhadap peningkatan kemampuan berpikir kritis matematis dan motivasi belajar peserta didik. Kemampuan berpikir kritis matematis dan motivasi belajar peserta didik yang menggunakan pembelajaran flipped classroom lebih baik dibandingkan kemampuan berpikir kritis matematis peserta didik yang menggunakan pembelajaran ekspositori.